2002
DOI: 10.2460/javma.2002.220.466
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serum thyroid hormone autoantibodies in dogs with clinical signs of hypothyroidism

Abstract: Thyroid hormone autoantibodies may falsely increase measured triiodothyronine (T3) and thyroxine (T4) concentrations in dogs; results suggest that T3 concentration may be falsely increased in approximately 57 of 1,000 dogs with hypothyroidism and that T4 concentration may be falsely increased in approximately 17 of 1,000 dogs with hypothyroidism. Results also suggested that dogs of certain breeds were significantly more or less likely to have THAA than were dogs in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
73
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(83 citation statements)
references
References 11 publications
3
73
0
7
Order By: Relevance
“…Lymphocytic thyroiditis is known to be highly heritable, and an influence of breed on age and progression of this disease has been demonstrated. 16,17 Dogs that were positive or inconclusive for TgAA (but had normal T4, FT4, and TSH concentrations) were not excluded from the analyses reported in our study because mean T4, FT4, and TSH concentrations were not different from those determined for TgAA-negative dogs, and their removal did not significantly change the results. These results agree with a study of human subjects where it was determined that there was minimal influence of antithyroid antibodies on the TSH reference range.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Lymphocytic thyroiditis is known to be highly heritable, and an influence of breed on age and progression of this disease has been demonstrated. 16,17 Dogs that were positive or inconclusive for TgAA (but had normal T4, FT4, and TSH concentrations) were not excluded from the analyses reported in our study because mean T4, FT4, and TSH concentrations were not different from those determined for TgAA-negative dogs, and their removal did not significantly change the results. These results agree with a study of human subjects where it was determined that there was minimal influence of antithyroid antibodies on the TSH reference range.…”
mentioning
confidence: 96%
“…These autoantibodies can interfere with the immunological measurement method and result in falsely elevated T4 concentration. 17 In our study, T4AA and T3AA were not measured. However, previously, it has been demonstrated that the presence of T4AA and T3AA did not result in falsely elevated thyroid hormone results when the chemiluminescence immunoassay b utilized in the current report was used.…”
mentioning
confidence: 99%
“…Although once daily dosing results in more fluctuation in serum T 4 concentrations compared to twice daily dosing, the duration of action of T 4 is longer than its plasma half‐life 22, 23, 24, 25, 26. In previous studies of the HPTA, dogs were administered levothyroxine twice daily, making comparisons difficult 6, 14…”
Section: Discussionmentioning
confidence: 99%
“…Only 17% of serum samples showed the presence of TPOAB, thus the parameter cannot be used for diagnosing lymphocytic thyroiditis in dogs. The presence of antibodies against thyroid hormones was tested, among others, by Nachreiner et al (18). The authors observed T3 and T4 antibodies in 6.3% of the tested dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Only when the animal has characteristic clinical symptoms, which can be assessed during clinical examination, and the remaining results of laboratory tests confirm the suspicion of the thyroid disease, TgAb s identification can be the basis for diagnosing hypothyroidism caused by lymphocytic thyroiditis. As a genetic susceptibility to lymphocytic thyroiditis has been described, it seems rational to perform such tests in breeding dogs (2,18,21). It also seems to be advisable to propose the owners of dogs used in breeding programmes, especially of breeds considered to be prone to hypothyroidism, to carry out prophylactic screening tests aiming at selecting animals with the TgAb s .…”
Section: Discussionmentioning
confidence: 99%